P005 DELAY IN DIAGNOSIS OF ULCERATIVE COLITIS: RESULTS OF A GLOBAL ULCERATIVE COLITIS NARRATIVE SURVEY. (7th February 2019) - Armuzzi, Alessandro; Kayhan, Cem; Panaccione, Remo; Watanabe, Kenji; Molander, Pauliina; Rubin, David T; Peyrin-Biroulet, Laurent; Melmed, Gil; Connor, Susan; Colombel, Jean-Frederic; Dubinsky, Marla
Abstract: Objective: The Ulcerative Colitis (UC) Narrative is a global survey of patients (pts) and gastroenterology physicians (GIs) aimed at identifying the impact of UC and comparing and contrasting perceptions of UC burden and management approaches. We examine UC diagnosis from a pt perspective, and the role of the GIs in early diagnosis and pt education. Here, we present data from 2100 pts and 1254 GIs in Australia, Canada, Finland, France, Germany, Italy, Japan, Spain, the UK, and the USA. Methods: Surveys were conducted online and by phone by The Harris Poll between August 2017 and February 2018. Eligible adult pts with UC (confirmed by endoscopy) were those who had visited a GI in the previous 12 months and had ever received prescription medication for UC. Self-reported medication history was used as a proxy for disease severity, with pts with moderate to severe UC defined as pts who had ever taken immunosuppressants, tumor necrosis factor inhibitors, other biologics, or corticosteroids for >4 of the past 12 months. Pts who had only ever taken 5-aminosalicylates or had a colectomy were excluded. Eligible GIs were those who saw ≥10 UC pts each month (≥5 in Japan), of whom ≥10% were taking a biologic and did not practice in a long-term care facility or hospice. Data are presented from all respondents who consented and completed the survey. Results: Mean pt age was 40.8 (standard deviation [SD] 12.4) years; 82% had moderate to severe UC and 67% self-described their UC as controlled with few to no symptoms. GIs saw a mean of 40 (SD 37.2) pts with UC each month. Pts typically experienced initial symptoms at a mean age of 30.0 (SD 12.7) years. It took a mean of 2.0 (SD 5.4) years between symptoms and UC diagnosis; 42% of pts waited ≥1 year for diagnosis, and 11% of pts had waited 5 years or more (Table). At the time of the survey, pts were a mean of 8.8 (SD 9.2) years post-diagnosis and had experienced 4.3 (SD 7.4) flares on average in the past 12 months. Thinking back to initial diagnosis, most pts expressed a desire to know where to find information and support (72%) or information on all available medications (74%). Many GIs (39%) felt that reliable advice on where to get information to help their pts manage their disease could help improve their pt relationships. 42% of pts felt that their GI could better explain how to access information and support from pt organizations. Of those pts who had interacted with pt organizations, 72% wished they had known about them earlier. Conclusion: In this large survey, we identified a mean of 2.0 years between UC symptom onset and diagnosis. Following diagnosis, pts continue to experience flares, which indicates poor disease control. There remains a great need for better information and materials to educate and assist in UC management.